Implementasi Pembelajaran Humanisme Dalam Pembelajaran Pendidikan Agama Islam Di Era Modern - Shodikun Shodikun; Esti Zaduqisti; Muhamad Rifa'i Subhi (https://ejournal.insuriponorogo.ac.id/, 2023)
The purpose of writing this work is to analyze the challenges of the modern era for Islamic religious learning and the implementation of humanism learning. Literature review as an effective approach in collecting, analyzing, and synthesizing information related to the implementation of humanism learning in Islamic religious education in the modern era. With systematic steps, this research enables the identification of relevant principles of humanism, strategies, benefits, and challenges. The results of this literature review research provide a deep understanding and an important contribution to the development of Islamic religious education in accordance with the demands of the times. This method also offers a solid theoretical foundation for understanding the relationship between humanism and Islamic religious education. The results of this study are that learning Islam in the modern era is faced with complex challenges such as the integration of technology with religious values and contextual understanding in a multicultural environment. Solutions that can be implemented include developing an online learning platform that pays attention to religious values and promoting inclusive understanding between religions. Strengthening religion-based character education and integrating Islamic religious studies with other subjects in an interdisciplinary manner are also important in responding to this challenge. The implementation of humanism learning can form an inclusive, empowered, and noble generation in Islamic religious education, but challenges such as the integration of humanist values with religious teachings and improving the quality of education need to be overcome to be successful.